Romania’s transnational constitution : a tradition of elite learning and self-empowerment - Parau, C (Cambridge University Press, 2013)
This chapter takes as its starting point a substantial modification of the constitutional diffusion theory outlined in this section. Its theorization features actors instead of states, as the latter conception is too abstract and remote from the actual causes and motives that bring about constitutional diffusion (Hirschl 2013). By inquiring into agency, it is hoped that the black box of one East European State – Romania – may be opened up in order to find out who the actors are who actually conceived and drafted the several constitutions Romania has had since the eighteenth century, and what motivated them. In every instance nearly all the actors proved to be elites, corroborating those who claim that “the people” are in fact little involved in constitutional conjunctures (Galligan 2013). The conceiving and drafting of constitutions has always been the domain of social elites and of “political entrepreneurs” originating within this class who chose to involve themselves in public affairs. The latter have always been a minority within a minority, an elite stratum of the social and economic elite.